Generational Reproduction of child abuse - García Ampudia, Lupe (2008)
The objective of this research is the study of the abuse rising in two generations, of parents and children and establishing the relationship between background child’s abuse with the potential abuse. The sample is comprised of 441 students and 303 parents who agreed to answer the Memories of Abuse Questionnaire. The used instruments were the Child History Questionnaire adapted for the purpose of this research, the Inventory of Potential Child Abuse (Milner, J. 1977), adapted by De Paul, Arruabarrena, Múgica and Milner, 1999 in Spain. The results show that both of them (parent and child) the emotional abuse is more frequently followed by physical and sexual abuse, comparing the two generations, the parents show a higher prevalence of abuse. Also the potential for abuse is significantly associated with history of physical abuse and emotional abuse and the children`s abuse is significantly associated with a parents abuse history, however also reported that the reproductive cycle of generational abuse is not all.